Transferable Immunoglobulin A–Coated Odoribacter splanchnicus in Responders to Fecal Microbiota Transplantation for Ulcerative Colitis Limits Colonic Inflammation - Lima, Svetlana F.; Gogokhia, Lasha; Viladomiu, Monica; Chou, Lance; Putzel, Gregory; Jin, Wen-Bing; Pires, Silvia; Guo, Chun-Jun; Gerardin, Ylaine; Crawford, Carl V.; Jacob, Vinita; Scherl, Ellen; et al. (Gastroenterology (New York, N.Y. 1943), 2022)
Fecal microbiota transplantation (FMT) is an emerging treatment modality for ulcerative colitis (UC). Several randomized controlled trials have shown efficacy for FMT in the treatment of UC, but a better understanding of the transferable microbiota and their immune impact is needed to develop more efficient microbiome-based therapies for UC. Metagenomic analysis and strain tracking was performed on 60 donor and recipient samples receiving FMT for active UC. Sorting and sequencing of immunoglobulin (Ig) A–coated microbiota (called IgA-seq) was used to define immune-reactive microbiota. Colonization of germ-free or genetically engineered mice with patient-derived strains was performed to determine the mechanism of microbial impact on intestinal immunity. Metagenomic analysis defined a core set of donor-derived transferable bacterial strains in UC subjects achieving clinical response, which predicted response in an independent trial of FMT for UC. IgA-seq of FMT recipient samples and gnotobiotic mice colonized with donor microbiota identified Odoribacter splanchnicus as a transferable strain shaping mucosal immunity, which correlated with clinical response and the induction of mucosal regulatory T cells. Colonization of mice with O splanchnicus led to an increase in Foxp3+/RORγt+ regulatory T cells, induction of interleukin (IL) 10, and production of short chain fatty acids, all of which were required for O splanchnicus to limit colitis in mouse models. This work provides the first evidence of transferable, donor-derived strains that correlate with clinical response to FMT in UC and reveals O splanchnicus as a key component promoting both metabolic and immune cell protection from colitis. These mechanistic features will help enable strategies to enhance the efficacy of microbial therapy for UC. Clinicaltrials.gov ID NCT02516384. [Display omitted] Fecal microbiota transplantation is an emerging therapy to treat ulcerative colitis. These findings define strain transferability associated with clinical response and highlight the mechanisms of their immune impact.